2017
DOI: 10.1139/cjfr-2016-0233
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of the soil charcoal pool in relation to fire history in a boreal forest landscape

Abstract: Charcoal pools in boreal forest soils constitute considerable amounts of slow cycling organic matter that is important in the global carbon cycle. However, these pools are characterized by spatiotemporal variations that are not well understood. Here, we have analyzed the charcoal pool in 100 soil samples to determine charcoal stock species origin and how the size and age of this pool varies across different spatial scales in a Norwegian boreal forest landscape including forests that differ in terms of tree-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
(87 reference statements)
2
4
0
Order By: Relevance
“…Similar to our results, high spatial variability has been observed elsewhere (Ohlson et al, 2006(Ohlson et al, , 2009Kasin et al, 2017), as well as the common occurrence of charcoal/PyC at the interface of the organic and mineral layers (Cyr et al, 2005;Ohlson et al, 2009;Hart and Luckai, 2014;Soucémarianadin et al, 2015a). Our depth profiles also show charcoal layers within the organic horizon of some LO plots.…”
Section: Comparison Of Amountssupporting
confidence: 90%
“…Similar to our results, high spatial variability has been observed elsewhere (Ohlson et al, 2006(Ohlson et al, , 2009Kasin et al, 2017), as well as the common occurrence of charcoal/PyC at the interface of the organic and mineral layers (Cyr et al, 2005;Ohlson et al, 2009;Hart and Luckai, 2014;Soucémarianadin et al, 2015a). Our depth profiles also show charcoal layers within the organic horizon of some LO plots.…”
Section: Comparison Of Amountssupporting
confidence: 90%
“…The soil BC in unburned plots may be caused by historical forest fires. Repeated fires could consume a portion of soil BC previously accumulated [14]. In addition, wildfires may result in soil erosion which could deliver soil BC to rivers [55] and to the mountain hill foot [56].…”
Section: Factors Affecting Soil Bc Distributionmentioning
confidence: 99%
“…BC is widespread in sediments and soils because of its refractory nature and the common occurrence of combustion [8][9][10]. Some studies have shown that much of BC is stored in boreal forest soils [11][12][13][14]. In addition, fire frequency will increase in boreal forest ecosystems with the climatic warming [15] and this trend could be further enhanced by the end of this century [16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, soil charcoal analysis from North America covering the Holocene found 'no decrease of charcoal mass with time' (De Lafontaine et al 2011, 572). Conversely, several studies from Eastern Norway argue that charcoal degradation in natural soil profiles (podsol) are heavily dependent on recurring forest, most importantly forest fires (Bjune et al 2013;Kasin et al 2017;Olhson et al 2017). Until regional empirical models for the correction of the radiocarbon date record in for example Eastern and Western Norway are constructed, application of more general models on the STAGED dataset, such as the exponential function proposed by Surovell et al (2009), is not recommended by the author and was not applied in this study.…”
Section: Methodsmentioning
confidence: 99%